Analisis Biaya dan Strategi Pengembangan Tanaman Pala - Jeter D Siwalette (Jurnal Indonesia Sosial Sains, 2022)
This study aimed to identify internal and external factors in the development of clove farming This research was conducted in Lilibooi village with the reason that this location is one of the central production of clove in West Leihitu District, Central Maluku Regency The sampling method used in this research was simple random sampling. The determination of samples used the Slovin formula, with a total sample of 65 respondents. The results showed that the development of clove farming carried out by farmers included internal factors such as production, income, expenditure, and revenue, while external factors such as technology and natural conditions. The development strategy of clove in Lilibooi village is 1. Optimally utilizing government support and extension workers in clove farming, 2. Making land effective, 3. Increasing the role of extension workers and agricultural institutions in transferring clove farming technology, 4. Opening up to living in groups, 5. Utilizing the existing clove collectors, 6. Setting the floor price and ceiling price, 7. Increasing clove value-added, and 8. Exchange ideas with other farmers.